Penggunaan Examples Based Learning (EBL) dalam Meningkatkan Level Kemampuan Berpikir Mahasiswa Berdasarkan Taksonomi Marzano Materi Metabolit Sekunder Mata Kuliah Bioteknologi - Mimi Halimah; Adi Rahmat; Sri Redjeki; R Riandi (Biosfer : Jurnal Biologi dan Pendidikan Biologi, 2021)
The thinking ability of pre service Biology teacher students must have high-level thinking skills, because they are prospective teachers for the millennial generation, therefore it is necessary to measure students' thinking levels so that prospective Biology teachers can prepare themselves from the start in an effort to improve their students' thinking skills in the future. This study aims to determine the level of students' thinking skills based on Marzano's (1997) taxonomy which includes Level 1: Retrieval, Level 2: Comprehension, Level 3: Analysis, Level 4: Knowledge utilization, Level 5: Metacognitive, Level 6: Self system. The method used in this research is one group pre test post test design. The results showed that there was a significant difference between the pre-test scores (M=27.42, SD=11.73) and post-test scores (M=65.22, SD=13.96) with the average N-gain being 0.52 which is in the medium category. Meanwhile, for the level of thinking ability, it shows that the highest contribution to increasing the average score is at level 2, namely comprehension and level 3, namely analysis, with each increasing score of 49 points. Level 6, which is the self system, also increased almost the same, as much as 48 points. Based on the results of these studies, it can be concluded that Examples Based Learning can increase the level of students' thinking skills